FYProCom Carnival - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 30 August 2021 - Congratulations to all the winners of FK Final Year Project Competition (FYProCom). The FYProCom Carnival was conducted online for Students Final Year Projects in Semester 2, Session 2020/2021.